2015
DOI: 10.2196/jmir.4153
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Persuasion Online: A Qualitative Study of Two Provaccine and Two Vaccine-Skeptical Websites

Abstract: BackgroundCurrent concerns about vaccination resistance often cite the Internet as a source of vaccine controversy. Most academic studies of vaccine resistance online use quantitative methods to describe misinformation on vaccine-skeptical websites. Findings from these studies are useful for categorizing the generic features of these websites, but they do not provide insights into why these websites successfully persuade their viewers. To date, there have been few attempts to understand, qualitatively, the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 46 publications
2
63
1
2
Order By: Relevance
“…Our method not only shows that these pairwise relations are the key part of the conversations, but also reveals how actants are related in a context-dependent manner. Grant et al [5] provide clear evidence for the impact of personal experience narrative on vaccination attitudes through the qualitative comparison of 4 websites. Kitta [22], who worked with a similar structural model for vaccine narrative, develops an important typology of vaccine stories, whereas Kata [3] determines the tropes that are functional on anti-vaccine websites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our method not only shows that these pairwise relations are the key part of the conversations, but also reveals how actants are related in a context-dependent manner. Grant et al [5] provide clear evidence for the impact of personal experience narrative on vaccination attitudes through the qualitative comparison of 4 websites. Kitta [22], who worked with a similar structural model for vaccine narrative, develops an important typology of vaccine stories, whereas Kata [3] determines the tropes that are functional on anti-vaccine websites.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, people are inclined to believe first-hand accounts from members of their community, as opposed to official pronouncements [5]. Social network theory has established a strong tendency toward homophily in online communities that often results in shared trust between community members [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has mostly been done by investigating the rhetorical strategies used by vaccine critics to convince their audience, such as reliance on anecdotes rather than statistics, emotive appeals, use of pictures, selfpresentations as "martyrs" or "underdogs" or representatives of "real Science," etc. 3,7,8,40,43,47,48,54,68 Most of these studies have focused on the discourse published by vaccine critics (tone, arguments, themes, style) with a focus on one specific form of internet use: active research of information by the individual in order to make a decision on the subject of vaccination. One way to move forward, building on the results obtained through this perspective, would be to shift the gaze toward the many ways in which vaccine criticism can circulate on the Internet in more complex and interactive ways than by just being available via the common tools of web research.…”
Section: How Vaccine Critical Actors Influence the Public Through Thementioning
confidence: 99%
“…constitutes another open avenue of research on vaccine criticism on the Internet. While many studies have suggested that vaccine critics rely in some way on interactive ways to mobilize on the Internet, 3,5,7,38,39,42,43,48,50 for instance via the administration of private forums or the setting up of petitions, few researchers have investigated this phenomenon further (for exceptions, see refs. 34,40,51,52,54,56 ) and none have done so in a systematic way.…”
Section: How Vaccine Critical Actors Influence the Public Through Thementioning
confidence: 99%